Pinpointing Morphology and Projection of Excitatory Neurons in Mouse Visual Cortex - Zhang, Yalun; Jiang, Siqi; Xu, Zhengchao; Gong, Hui; Li, Anan; Luo, Qingming; Ren, Miao; Li, Xiangning; Wu, Hao; Yuan, Jing; Chen, Shangbin (Frontiers in Neuroscience, 2019)
The excitatory neurons in the visual cortex are of great significance for us to understand brain functions. However, the diverse neuron types and their morphological properties have not been fully deciphered. In this paper, we have applied the brain-wide positioning system (BPS) to image the entire brain of Thy1-eYFP H-line mouse at 0.2 × 0.2 × 1 μm3 voxel resolution. A total of 92 neurons have been reconstructed in the layers 5 and 6 of visual cortex with single-axon level resolution. Based on the complete topological of neurons and the inherent positioning function of imaging, we have classified the observed neurons as 6 types according to their apical dendrites and somata’s location. They are star pyramidal cell in layer 5 (L5-sp), slender-tufted pyramidal cell in layer 5 (L5-st), tufted pyramidal cell in layer 5 (L5-tt), spiny stellate-like cell in layer 6 (L6-ss), star pyramidal cell in layer 6 (L6-sp), and slender-tufted pyramidal cell in layer 6 (L6-st). By examining the projection patterns of individual neurons, they can be categorized into three modes: circuit connection neurons (ICCN), callosal projection neurons (CPN) and corticofugal projection neurons (CFuPN). Correlating the two kinds of classifications, we have found that there are at least two projection modes comprised in the former defined neuron types except L5-tt. On the other hand, each projection mode may consist of 4 dendritic types defined in this study. The axon projection mode just partially correlates with the apical dendrite feature. This work has demonstrated a paradigm to resolve visual cortex by single neuron quantification, and shown the potential to be extended to reveal the connectome of other defined sensory or motor system.